ANALISIS TEKNIK PENERJEMAHAN MAJAS IRONI DAN SARKASME DALAM NOVEL THE RETURN OF SHERLOCK HOLMES SERTA DAMPAKNYA TERHADAP KUALITAS TERJEMAHAN - Irene Dinari; Mangatur Nababan; Djatmika Djatmika (Prasasti: Journal of Linguistics, 2017)
Background: This research is conducted by analyzing figurative language as irony and sarcasm in the novel entitled The Return of Sherlock Holmes (TROSH) and its translation in Bahasa Indonesia. The aims of this research are to (1) identify such types of figurative language as irony and sarcasm in the novel TROSH and its translation in Bahasa Indonesia, (2) identify translation techniques used when translating the irony and sarcasm, (3) find out the translation shifts appearing as effects of the application of the translation techniques, and (4) find out the effects of the translation shifts of irony and sarcasm on translation quality considering accuracy, acceptability, and readability.